ANALISIS SISTEM MANAJEMEN SURAT TERKOMPUTERISASI UNTUK MENINGKATKAN KINERJA ADMINISTRASI - Sulung, Undari; Muspawi, Muhammad (Manajemen Pendidikan, 2023)
Efficient mail management is a crucial factor in ensuring the smooth operation of university administrative processes. In the digital era, the use of information technology to enhance administrative processes has become a necessity. This research aims to analyze the use of computerized mail management systems in improving the administrative performance of the Master of Natural Sciences (PMIPA) Program at the Faculty of Teacher Training and Education (FKIP) of Jambi University. The research method employed is qualitative research. Data was collected through a series of steps, including interviews with administrative staff and direct observation related to the use of computerized mail management systems. This research was conducted in October-November at the PMIPA Department of FKIP, Jambi University. The results of this study show that the computerized mail management system at PMIPA FKIP, Jambi University, has brought about significant positive changes in administration by improving efficiency, accessibility, and transparency. Despite some challenges that need to be addressed, such as internet connection stability, staff training, and sustainable system maintenance, the use of this technology has helped simplify administration and minimize paper usage, creating a more modern and responsive administrative environment for the future